2007
DOI: 10.1175/jcli3987.1
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Extreme Rain Events in Satellite Rain-Rate Estimates and an Atmospheric General Circulation Model

Abstract: The frequency distributions of surface rain rate are evaluated in the Tropical Rainfall Measuring Mission (TRMM) and Special Sensor Microwave/Imager (SSM/I) satellite observations and the NOAA/GFDL global atmosphere model version 2 (AM2). Instantaneous satellite rain-rate observations averaged over the 2.5° latitude × 2° longitude model grid are shown to be representative of the half-hour rain rate from single time steps simulated by the model. Rain-rate events exceeding 10 mm h−1 are observed by satellites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
136
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(141 citation statements)
references
References 32 publications
3
136
0
2
Order By: Relevance
“…Probability densities are much higher at high rain rates for the 4 km model runs and TRMM, while below about 1 mm h −1 the 12 km param model probability densities are much higher than those of the observations and other models. The fact that the 12 km param model has far too much light rain agrees with many earlier analyses of weather and climate models using convective parametrizations (Dai and Trenberth, 2004;Sun et al, 2006;Wilcox and Donner, 2007;Stephens et al, 2010).…”
Section: Precipitation Distributionssupporting
confidence: 85%
See 1 more Smart Citation
“…Probability densities are much higher at high rain rates for the 4 km model runs and TRMM, while below about 1 mm h −1 the 12 km param model probability densities are much higher than those of the observations and other models. The fact that the 12 km param model has far too much light rain agrees with many earlier analyses of weather and climate models using convective parametrizations (Dai and Trenberth, 2004;Sun et al, 2006;Wilcox and Donner, 2007;Stephens et al, 2010).…”
Section: Precipitation Distributionssupporting
confidence: 85%
“…Many studies have shown that convective parametrizations generally lead to rainfall occurring at rates that are too small and over durations that are too long (Dai and Trenberth, 2004;Sun et al, 2006;Stephens et al, 2010), though there have been efforts to improve this behaviour (Wilcox and Donner, 2007). Observations over tropical regions show roughly power-law behaviour of precipitation distributions at lower rain rates, with faster, exponential decreases as very high rain rates are approached (DeMott et al, 2007;Field and Shutts, 2009;Peters et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the uncertainty in changes in upward velocities in climate-model simulations is thought to relate to parameterized moist convection 38,39 which is more important for warm season or tropical precipitation, even if convection may enhance snowfall locally in a given storm. Consistent with this interpretation, extratropical precipitation extremes are generally found to respond to climate change in a robust manner, unlike tropical precipitation extremes 12,39 .…”
Section: Derivation Of Theory For Snowfall Extremesmentioning
confidence: 99%
“…The variations among models in the tropics indicate that simulated precipitation extremes may depend sensitively on the parameterization of unresolved and poorly understood processes such as moist convection (9). Indeed, climate models do not correctly reproduce the interannual variability of precipitation extremes in the tropics (10), or the frequency and intensity distribution of precipitation generally (9,11,12).It is difficult to use the relatively short observational record to quantify long-term global trends in precipitation extremes (13)(14)(15). Observations of interannual variability indicate that tropical precipitation extremes exhibit a greater sensitivity to temperature change than they would if they scaled with atmospheric water vapor content (10).…”
mentioning
confidence: 99%
“…The variations among models in the tropics indicate that simulated precipitation extremes may depend sensitively on the parameterization of unresolved and poorly understood processes such as moist convection (9). Indeed, climate models do not correctly reproduce the interannual variability of precipitation extremes in the tropics (10), or the frequency and intensity distribution of precipitation generally (9,11,12).…”
mentioning
confidence: 99%